Executive function in Singaporean preschoolers. - Ng, Li Sha. (2012)
Executive Function (EF) is a set of cognitive processes that regulates goal-directed behavior. The current study aimed to investigate the development of EF and the structure of EF in Singaporean preschoolers. Four-year-olds (N = 46) and five-year-olds (N = 28) were tested with eight EF tasks, including the Self-Ordered Pointing Task (SOPT), the Dimensional Change Card Sorting task (DCCS), the Go/No go task, the Delay of Gratification task (DOG), the Flexible Items Selection Task (FIST), the Auditory Working Memory task (AWM), the Planning task, and the Intra-Dimensional/Extra-Dimensional shift (ID/ED). These tasks sought to measure working memory, inhibitory control, flexibility, and planning. Results showed that children’s performance on the Compound Reversal of the ID/ED shift, Go trials of the Go/No go task, DOG, FIST, and AWM improved, indicating a rapid development of EF between four and five years of age. Additionally, cluster analysis showed a single cluster, suggesting a unitary EF model.